Pengembangan Digital Flipbook berbasis Dolanan Lokal untuk Meningkatkan Literasi Membaca Siswa SD di Desa Palaan pada Era Covid-19 - Tety Nur Cholifah; Adzimatnur Muslihasari (Universitas Kanjuruhan Malang, 2022)
The purpose of this study was to produce a digital flipbook based on local games to improve the reading literacy and reading literacy. The method used is the research method (R&D), researching potential and problems, gathering information, product design, design validation, design revision, initial trial, product revision, usage trial, and product revision. Data analysis used descriptive percentage and N-gain test. The results of the study were based on the average value of the validity test on digital flipbooks based on local games in the media field 94%, material field 93%, reading literacy instrument field 93%, and student response field 95%, with criteria for all fields